Corporate Equity Ownership and the Governance of Product Market Relationships - FEE, C. EDWARD; HADLOCK, CHARLES J.; THOMAS, SHAWN (Journal of Finance, 2006)
ABSTRACT We assemble a sample of over 10,000 customer–supplier relationships and determine whether the customer owns equity in the supplier. We find that factors related to both contractual incompleteness and financial market frictions are important in the decision of a customer firm to take an equity stake in their supplier. Evidence on the variation in the size of observed equity positions suggests that there are limits to the size of optimal ownership stakes in many relationships. Finally, we find that relationships accompanied by equity ownership last significantly longer than other relationships, suggesting that ownership aids in bonding trading parties together.